The Existence of Traditional Games for Elementary School-Age Children in Tuah Karya Village - Nurhayati, Nurhayati; Jamaris, Jamaris; Marsidin, Sufyarma; Hadiyanto, Hadiyanto; Solfema, Solfema; Gistituati, Nurhizrah; Iswari, Mega (Sosial Budaya, 2022)
Traditional games as a cultural heritage need to be explored and socialized so that they are not interrupted and to avoid extinction. Traditional games are very beneficial for the physical, social, and emotional growth and development of children. The existence of traditional games in the era of globalization has begun to be replaced by technology-based games. This study aimed to determine the existence of traditional games among elementary school children in Tuah Karya Village, Tuah Madani Sub-district, Pekanbaru City. The population of this study was elementary school-aged children who live in the Tuah Karya Village, with a total of 2.208 people. A total of 110 samples were taken by random sampling technique. Data collection techniques were carried out using questionnaires and percentage descriptive data analysis techniques. The results of the study show that traditional games in Tuah Karya Village can be classified into three categories: there are traditional games that still exist, are almost extinct, and are no longer recognized. There are seven games that still exist: kelereng, gasing, layang-layang, lompat tali  (yeye), statak, congkak, and tarik tambang. The five almost extinct games are ular naga dan anak ayam, petak umpet, eggrang, and terompa panjang. The seven games that are no longer recognized are ligu, canang (gatrik), meja pari, adu buah para (buah karet), benteng, boi-boian, and lulu cina buta. The existence of traditional games in the Tuah Karya Village can still be improved because the situation and conditions in the area are still conducive.